The Dynamics of the Role of the Nahdlatul Ulama Social Movement in Responding to Social Change - Saepulah Saepulah; Lina Herlina; Unang Fauzi (UIN Sunan Gunung Djati Bandung, 2020)
The purpose of this study is to uncover sociological and cultural conclusions about community dynamics in various dimensions. The method used in this research is to conduct a literature review relating to the historical trajectory of Nahdhatul Ulama (NU) as a primary data source. Besides, an analysis of various data and information obtained from literature and journals as a source of secondary data. Based on the results of data and information processing, it is concluding that NU, as a social organization in the religious, social movement, has a significant contribution to the socio-religious dimension. Contributions include spiritual, social, educational, environmental, and economic preservation, including improving communication between scholars, improving the quality of Islamic schools, selecting books studied in Islamic boarding schools, and establishing bodies to support agricultural activities and Muslim trade.